Evaluation of dietary taurine concentrations in microparticulate diets provided to larval California yellowtail (Seriola dorsalis) postlarvae. (16th March 2017) - Stuart, K.; Hawkyard, M.; Barrows, F.; Rust, M.; Drawbridge, M.
Abstract: Taurine is an important amino acid derivative for marine and freshwater fish, especially during early development. We investigated the range of taurine concentrations that influence the growth and survival rates of California yellowtail (CYT; Seriola dorsalis ) during transition from live feeds to microparticulate diets, as well as the extent to which nutrient leaching from the microparticulate diets affects these ranges. We tested particle‐assisted rotationally agglomerated (PARA) particles with four levels of taurine: 4 (low taurine; LT), 45 (medium taurine; MT), 93 (high taurine; HT) and 122 g/kg (very high taurine; VHT). Our results showed that CYT postlarvae had no significant differences in growth, survival and feed consumption rates between the MT, HT and VHT treatments. However, it should be noted that the PARA particles containing 122 g/kg (VHT) taurine were especially prone to leaching and may have had taurine concentrations as low as 34.9 g/kg before they settled on the bottom of the tank. Therefore, the actual dietary taurine concentrations experienced by the larvae were likely lower than the initial dietary concentrations. More research is needed to evaluate the potential nutrient toxicity of elevated dietary taurine concentrations for marine fish larvae and juveniles.